Criminal Accountability For The Fulfillment Of Restitution For Children As Victims Of The Crime For Human Trafficking Study Decision Number: 79/Pid.Sus/2020/Pn.Olm - Br Gultom, Nabila Putri Aprilia; Syahranuddin, Syahranuddin (Fakultas Hukum Dehasen, 2026)
Trafficking in persons involving child victims is a serious crime that requires legal protection not only through the punishment of offenders but also through the restoration of victims’ rights through restitution. This study analyzes the legal regulation of criminal liability for the fulfillment of restitution for child victims of trafficking, as well as the role of judges, through a case study of Decision Number 79/Pid.Sus/2020/PN.Olm and Appellate Decision Number 100/PID/2020/PT KPG. This research employs a normative juridical method with statutory and case approaches. The findings show that restitution has been normatively regulated under Law Number 21 of 2007 but has not been optimally implemented in judicial practice. Judges have not maximized their authority, and appellate judges have failed to perform a corrective function, indicating the need to strengthen the judicial role through child-protection-oriented and restorative justice–based approaches.